The Influence of Earnings Per Share, Return on Assets, and Debt to Equity Ratio on Stock Prices of Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) - Salihi, Said Saleh; Hwihanus, Hwihanus (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
This study aims to analyze the influence of Earnings Per Share (EPS), Return On Asset, and Debt to Equity Ratio on the Stock Prices of Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2021-2023 period. The results of this study are expected to serve as a foundation and reference for analyzing the effect of Earnings Per Share (EPS), Return On Asset, and Debt to Equity Ratio on Stock Prices in the capital market. To obtain data, the author used documentation and literature study methods, while the analysis technique employed was multiple linear regression. The research results tested with the Coefficient of Determination (R Square) showed that Earnings Per Share (EPS), Return on Asset, and Debt to Equity Ratio contribute to Stock Prices by 63.6%. The t-test results indicated that the variables Earnings Per Share (EPS), Return on Asset, and Debt to Equity Ratio do not have a significant individual effect on Stock Prices. The F-test results showed that the variables Earnings Per Share (EPS), Return on Asset, and Debt to Equity Ratio collectively have a significant effect on Stock Prices.